New Age Herbals Resource, Quality and Pharmacognosy (Singapore : Springer Singapore, 2018)
Importance of herbs (medicinal plants) can hardly be overemphasized. They are exploited for manyfold applications, ranging from phytopharmaceuticals, to nutraceuticals, to cosmetics and many others. Keeping in view the richness of herbs and their vast potential, this book collates the most up-to-date knowledge of important herbs and herbals. The book also gives an overview of some issues causing hindrance in the promotion of herbals. This book attempts to compile the rich experience of experts working on various herbs. New age single plant species, having multiple medicinal traits worth exploiting i.e. Hippophae rhamnoides (seabuckthorn), and Morinda citrifolia (noni) also find place as full chapters in the book.
1. Introduction -- Part I - 2. Research and Development on Artemisia annua in India -- 3. Indian Sea Buckthorn -- 4. Noni (Morinda citrifolia L.): Research and Development -- 5. Rhodiola: An Overview of Phytochemistry and Pharmacological Applications -- 6. Ophiocordyceps sinensis: The Medicinal Caterpillar Mushroom -- 7. Indian Hawthorn (Pyracantha crenulata) -- 8. Advancement in Medicinal Mushroom Research -- 9. Biotechnological Strategies for Improvement of Withania somnifera (L.) Dunal -- Part II - 10. Quality Control of Herbal Drugs: Advancements and Challenges -- Part III - 11. Cultivation and Bioprospecting of Medicinal Plants -- 12. High-Yielding Improved Varieties of Medicinal and Aromatic Crops for Enhanced Income -- 13. Indian Plant Genetic Resources of Medicinal Value -- 14. Common Pests and Diseases of Medicinal Plants and Strategies to Manage Them -- 15. Biodiversity Conservation in Medicinal Plants and Protection of Plant Varieties and Farmers' Rights Act -- Part IV - 16. Exploring the Medicinal Value of Green Wealth with Special Reference to Neuronutrient Medhya Rasayana Plant Drugs -- 17. Medical Radiation Countermeasures for Neuroprotection: Herbal Solutions, Evidences and Challenges Therein -- 18. DRDO Herbal Technologies: Military and Civil Applications -- 19. Herbals for Animal Health and Better Production -- 20. Medicinal Plants as Novel Promising Therapeutics for Neuroprotection and Neuroregeneration -- 21. Phytosomes: The Novel Drug Delivery System for Phytomedicine.
Biomedical and Life Sciences
text file PDF
Keywords: Pharmacology; Biomedical engineering; Plant breeding; Health promotion; Veterinary medicine